The Effects of Abduction in the Community in Barangay Pasong Putik Quezon City: Vol.4, No.1 (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
This study aims to determine the effects of abduction in the community at Barangay PasongPutik Quezon City. The study utilizes a descriptive research method, which was used togather information from respondents in accordance with the posed questions.The results of this study show that abduction had an effect on the community, and it can alsoaffect their daily lives. The result also revealed that the effects might be psychological andbehavioral effects that can lead to poor communication with others and a lack of socializing.This study recommended that the barangay should conduct seminars for its residents withregard to what to do when there’s an abduction, as stated in our background of the study.Abductions may happen at any time of any day or night, at we least expect them to; thebarangay has helped to take care of its citizens by giving them the knowledge they need tolessen or prevent any worst-case scenarios during such an event. It’s not just the Philippinesthat is experiencing an increase in abductions; there are other nations that are alsoexperiencing this problem. Abductions are becoming more unpredictable by the day; it’spreferable to be ready for the worst rather than hoping for the best and suffering the effectslater. The implications of this study could be used to determine how the abduction can affectevery individual who experienced abduction and how they will manage to support and helpothers who encounter the abduction.
Keywords: Criminology